Sifat anti-rayap zat ekstraktif beberapa jenis kayu daun lebar tropis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The using of conventional wood preservatives would be facing a big problem from the environmental dimension. Therefore the development of the new type of preservatives will be one of the most social demanded subject. One of the new type of preservatives which can be examined from the tropical forest is wood extractives which has toxicity to the termite and fungal attack. The aim of this study is to evaluate the antitermitic properties of extractives from some tropical hardwoods to the termite attack of Coptotermes curvignathus Holmgren. The heartwood of samples were converted into woodmeals in a Willey mill with 40 - 60 mesh screen, and air-dried to about 15 % of moisture content. Acetone extracts solution obtained from wood sample was successively fractionated into n-hexane, ethyl ether, and ethyl acetate soluble fractions. Each fraction was then subjected to the antitermite bioassay tests. The antitermite bioassay test showed that n-hexane fraction of Sonokembang wood, n-hexane fraction from Ebony wood, and the insoluble fraction of Torem wood are very toxic to the termite of C. curvignathus. The chemical identification by using GCMS showed that from n-hexane fraction of Sonokembang wood three compounds were identified, while from n-hexane fraction of Ebony wood and insoluble fraction of Torem wood were five compounds and three compounds, respectively.